COMMUNITY PERCEPTION OF THE HOPE FAMILY PROGRAM TO INCREASE SOCIAL WELFARE OF POOR FAMILY IN HULU SIHAPAS DISTRICT, PADANG LAWAS UTARA - Pertama Yul Asmara (Jurnal Ekonomi, 2022)
This study aims to describe and explain the community's perception of the hopeful family program in improving the social welfare of poor families in Hulu Sihapas District, North Padang Lawas. The Family Hope Program (FHP) is a program that provides cash assistance to poor families, if they meet the requirements related to efforts to improve the quality of human resources, namely Education, Health and Social Welfare. The FHP program is a program created by the Indonesian Ministry of Social Affairs based on the Decree of the Coordinating Minister for Poverty. This study aims to discuss the implementation of the Minister of Social Affairs Regulation Number 1 of 2018 concerning the Family Hope Program in Providing assistance to the Poor in Hulu Sihapas District, Padang Lawas Utara, Bantan District, and to examine the factors that become obstacles in providing assistance to the poor in the District. Hulu Sihapas, Padang Lawas Utara, Bantan District. This type of research is descriptive qualitative research, the research approach is a sociological approach. Sources of data obtained from primary data and secondary data. In data collection techniques, researchers used interviews, and documentation. The data analysis techniques used in this research are data reduction, data presentation and conclusion drawing. The results of this study are: firstly that the implementation of the Minister of Social Affairs Regulation Number 1 of 2018 concerning the Family Hope Program in Providing assistance to the Poor in Hulu Sihapas District, Padang Lawas Utara is going quite well, it is proven that the recipients of the Family Hope Program (FHP) assistance affect the alleviation variable. Poverty in the District of Hulu Sihapas North Padang Lawas so that the government of the District of Hulu Sihapas North Padang Lawas must be able to maintain this assistance program so that the people of the District of Hulu Sihapas North Padang Lawas can be helped. Second, the constraints in this program include internal factors and external factors